Deposition of Steel over Steel by Friction Surfacing Technique and Investigation of its Physical Geometry (MIST International Journal of Science and Technology, 2023)
Friction surfacing (FS) is a coating technique inspired by friction stir welding. FS is a solid-state, thermo-mechanical process providing excellent wear and corrosion resistance properties. Frictional heating elevates the temperature of the consumable rotating tool (mechtrode) up to the softening of the material, the tool is traversed along the length of the plate, and the material gets deposited onto the substrate plate with good mechanical properties and excellent corrosion resistance properties, FS process may have wider application in the mining industry to provide an adequate coating on excavator's teeth, shovel teeth, and dragline teeth. This paper has an experimental approach to investigate the coating integrity during the FSed deposition of AISI4140 (consumable rod) over EN24 plate on a conventional milling machine. Various tests like wear test, XRD analysis, hardness, IR thermography, surface roughness, FESEM images have been analysed. Experiments have shown that at a low travel speed of 16mm/min, the coating is non-uniform and an excessive increase in travel speed will not give proper time for softening of the material, resulting in a discontinuous coating so the optimum travel speed must be chosen for better quality coating. Also, one more approach has been made to explore the effect of mechtrode shapes on the flash formation of the consumable tool while deposition of mild steel over mild steel on the milling machine where conical cylinder tool shape was more efficiently worked.MIJST, Vol. 11, December 2023 : 15-25DOI: https://doi.org/10.47981/j.mijst.11(02)2023.427(15-25)